The Effect of Effectiveness and Trust on the Use of Village Financial Systems on Village Government Performance - Sahusilawane, Wildoms (International Journal of Science, Technology & Management, 2021)
This study aims to determine the effect of effectiveness and trust in using the village financial system on village governments' performance in Maluku Province. This study's population is the village government apparatus consisting of the Village Head or Country, Village Secretary, village financial system users, amounting to 63 respondents; this study's sampling method is non-probability, namely purposive sampling. Primary data in this study include respondents' answers through questionnaires. The collected questionnaires using multiple correlations and regressions analysis, including descriptive statistics, reliability tests, validity tests, and classical assumptions, including multicollinearity tests and hypothesis testing and discussion. The F test analysis results show that the effectiveness and trust variables together have a positive and significant effect on the village government's performance. Based on empirical evidence with t-test or partial with multiple regression models, there is a positive and significant influence between the variables of effectiveness with the village government's performance and confidence in the village government's performance.